Educational Influencers on Instagram: Analysis of Educational Channels, Audiences, and Economic Performance - Javier Gil-Quintana; Emilio Vida de León (Publications, 2021)
Influencers have positioned themselves as opinion leaders capable of influencing large social groups, extending their presence to areas such as education. Instagram is one of the most consolidated social networks focused on the image where citizens interested in educational areas can find information from specialized channels on this topic. The purpose of this study is to analyze, during the period of confinement by COVID-19, the use of Instagram by educational influencers to consolidate their channel in new audiences, influence through interaction with their followers and create their transmedia production. Using a mixed methodological approach, a descriptive analysis of a sample of 810,200 users and a content analysis of 13 profiles of educational influencers is applied. The results show educational influencers as true experts in the use of Instagram, managing visually pleasing and harmonious profiles for new audiences. These influencers reach a large number of users, mostly women between the ages of 25 and 45 with an interest in “motherhood” on the platform. Educational influencers use digital marketing codes in their social networks, with a communicative style adapted to this type of space that seeks to increase the interaction and participation of new audiences and, as a consequence, economic profitability. There is a high number of influencers whose objective is to share educational resources, using their accounts as showcases for their transmedia educational production and for the sale or promotion of their productions and creations.